Kant’s normative moral theory: Apparent moral universalism and the challenge of persistent structural racism - Christel Fricke (Rivista di Estetica)
Kant is famous for his doctrine of moral universalism. But in his writings on anthropology, physical geography, and history, he distinguished between four different human races, claiming that only members of the white, European race had developed the capacity for rational and moral agency to a high degree of perfection. The question of how his apparent moral universalism relates to his racial moral particularism has led to a controversial debate. Was he an inconsistent moral universalist or a consistent moral particularist? Lu-Adler has convincingly argued that Kant’s defence of white moral supremacy is not incompatible with his moral universalism. What does this mean for the authority of his normative moral theory? Must we reject Kant’s moral theory and remove his writings from our reading lists? Or can we stand by him and trust that his racist views do not undermine the core of his claims about the necessary and objective moral duties we have? As I will argue, the structural racism that persists even among those who are committed to moral universalism and the equal worth of all human beings reveals a weakness in Kant’s ethics of conviction that should not be overlooked.